Sensing trace levels of molecular species in solution via zinc oxide nanoprobe Raman spectroscopy. (20th June 2017) - Cook, Andrew L.; Carson, Carcia S.; Marvinney, Claire E.; Giorgio, Todd D.; Mu, Richard R.
Abstract : Surface‐enhanced Raman spectroscopy (SERS) has potential for unique clinical, environmental, and military applications, among many others, but it is limited by a rapid decrease in signal with distance from the sensing surface. For this reason, much study of SERS‐based biosensing involves chemical or physical adsorption of analytes to an active surface. Adsorption, however, limits the types of analytes that can be detected and detection sensitivity. The three‐dimensional closely packed architecture of zinc oxide (ZnO) nanowires decorated with silver nanoparticles increases SERS intensity, allowing for adsorption‐free biosensing. This approach greatly expands the potential applications of Raman spectroscopy as a biosensing technique. This work demonstrates a significant SERS enhancement from silver nanoparticle‐decorated ZnO nanoprobes to the Raman spectra of crystal violet, melamine, and adenine solutions. These enhancements were quantified by comparing the intensity of Raman peaks from each of the three solutions through ZnO nanowires decorated with silver nanoparticles with that through bare ZnO nanowires. Estimated enhancement of the Raman signal accounted for the volume difference between solution affected by SERS and solution sensed by the Raman system. More importantly, the detected SERS signal is from molecules in solution and unadsorbed to the sensing surfaces. This lack of adsorption was confirmed by tracking the SERS enhancement of a crystal violet Raman peak over time. This greatly enhances the value and flexibility of Raman spectroscopy as a detection technique for a wide variety of applications. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A novel ZnO nanowire/Ag nanoparticle substrate was used for surface‐enhanced Raman spectroscopy (SERS) on crystal violet, melamine, and adenine in solution. Enhancement was quantified, and time‐dependent Raman analysis determined that the Raman signal is from molecules in solution and unadsorbed to the sensing surfaces.